Clinical and Experimental Determination of Protection Afforded by BCG Vaccination against Infection with Non-Tuberculous Mycobacteria: A Role in Cystic Fibrosis? - Sherridan Warner; Anneliese Blaxland; Claudio Counoupas; Janine Verstraete; Marco Zampoli; Ben J. Marais; Dominic A. Fitzgerald; Paul D. Robinson; James A. Triccas (Vaccines, 2023)
Mycobacterium abscessus is a nontuberculous mycobacterium (NTM) of particular concern in individuals with obstructive lung diseases such as cystic fibrosis (CF). Treatment requires multiple drugs and is characterised by high rates of relapse; thus, new strategies to limit infection are urgently required. This study sought to determine how Bacille Calmette-Guérin (BCG) vaccination may impact NTM infection, using a murine model of Mycobacterium abscessus infection and observational data from a non-BCG vaccinated CF cohort in Sydney, Australia and a BCG-vaccinated CF cohort in Cape Town, South Africa. In mice, BCG vaccination induced multifunctional antigen-specific CD4+ T cells circulating in the blood and was protective against dissemination of bacteria to the spleen. Prior infection with M. abscessus afforded the highest level of protection against M. abscessus challenge in the lung, and immunity was characterised by a greater frequency of pulmonary cytokine-secreting CD4+ T cells compared to BCG vaccination. In the clinical CF cohorts, the overall rates of NTM sampling during a three-year period were equivalent; however, rates of NTM colonisation were significantly lower in the BCG-vaccinated (Cape Town) cohort, which was most apparent for M. abscessus. This study provides evidence that routine BCG vaccination may reduce M. abscessus colonisation in individuals with CF, which correlates with the ability of BCG to induce multifunctional CD4+ T cells recognising M. abscessus in a murine model. Further research is needed to determine the optimal strategies for limiting NTM infections in individuals with CF.